PENGARUH BEBAN KERJA DAN MOTIVASI INTRINSIK TERHADAP KINERJA PEGAWAI PUSKESMAS SIMOLAWANG DENGAN KELELAHAN KERJA (BURNOUT) SEBAGAI VARIABEL MODERASI - Nur Azizah, Elia; Kistyanto, Anang; Dwijanto Witjaksono, Andre (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the effect of workload and intrinsic motivation on the performance of Simolawang Health Center employees with burnout as a moderating variable. This research uses quantitative approach with survey method. Data were collected through questionnaires distributed to 46 respondents who are employees at Simolawang Health Center. The sampling technique used purposive judgment sampling. Data analysis was carried out using a Structural Equation Model (SEM) based on Partial Least Square (PLS) to test the research hypothesis. The results showed that workload has a significant negative effect on employee performance, the higher the workload, the lower employee performance will be, the less workload, the employee performance will increase. Intrinsic motivation on employee performance of Simolawang Health Center, the results showed that intrinsic motivation has a significant positive effect on employee performance. However, burnout as a moderating variable proved to be not significant and did not play a role in having an impact on the relationship between workload and employee performance, burnout as a moderating variable is not significant and does not have an impact on the relationship between intrinsic motivation and employee performance. This study provides implications in the management of human resources in health centers in the preparation of the main tasks and work functions of employees to create a good and conducive work environment.